STAKEHOLDER SYNERGY IN EFFORTS TO OVERCOME TUBERCULOSIS (TB) IN MAKASSAR CITY - Ramdani, Lili Aulya; Guntur, Muhammad; Ismail, Ismail (Universitas Negeri Makassar, 2025)
This study aims to determine the Synergy of Stakeholders in Efforts to Overcome Tuberculosis (TB) in Makassar City. Where the type of research used is qualitative using data collection techniques, namely observation, interviews, and documentation. The data analysis techniques used are data condensation, data presentation, conclusion drawing and verification. Research that has been conducted shows that there is a role of stakeholders involved in efforts to control TB based on existing responsibilities and sectors. In addition, from the results of the study, the synergy carried out by stakeholders in efforts to control TB disease and in the TB Multisector Forum in Makassar City is still not optimal which can be seen through the synergy theory indicators by Doctoroff with four indicators, namely: Effective communication, fast feedback, trust, and creativity. It is said that it is not optimal because there are several indicators that are not in accordance with field conditions. The communication carried out is still not effective, which can be seen from the communication process involved in the Multisector Forum is not carried out regularly, socialization activities carried out to the community are not carried out directly, and there is no Regional Regulation on TB which can be a guideline that can bind stakeholders and the community to be involved in efforts to overcome TB. The feedback provided by stakeholders is still not optimal with a lack of awareness of responsibility as a stakeholder and the elimination of negative stigma as a response in society. In the indicators of trust and creativity that have been running as desired by each other's roles and by the existence of programs issued.